Membandingkan Kinerja Laser dan LED dalam Pencitraan Fluoresensi Buah Berondolan Kelapa Sawit - Minarni Shiddiq; Ria Fitriani (Jurnal Penelitian Sains, 2017)
Diode Lasers (LD) and light emitting diodes (LEDS) have been used for fluorescence imaging due to their low cost and wavelength varieties. The fluorescence Imaging has recently been developed as a nonde-structive method for fruit and vegetable quality assessments. This research was aimed to study the potential use of both light sources in fluorescence imaging techniques for grading palm oil fresh fruit bunches in attempt to develop a laser based grading system. The system consisted of a 650 nm LD and a 680 nm LED with the same 5 mW output power. and a monochrome CMOS camera with a camera lens, and a color filter. The filter used to obtain the fluorescene intensity was an orange filter. The samples were Tenera varieties of lonsum loosed palm oil fresh fruits with 4 ripeness categories determined by an experienced harvester. The categories were underripe (f0), ripe 1 (f1), ripe 2 (f2) and ripe 3(f3), each with 3 duplicates.The recorded images of the loosed fruits were analyzed using imageJ software, and further compared.The result showed that the highest fluorescence intensities represented by the gray values of the images were obtained from the underripe (f0) fruits, followed by the ripe 2 (f2), ripe 3(f3), and, ripe 1(f1) fruits, for both light sources.The intensity levels ob-tained using LD were higher by 75.32a.u for underripe (f0), 52.35 a.u for ripe 1(f1), 57.18a.u for ripe 2(f2), and 55.11 a.u for ripe 3(f3) than those resulted from LEDS by 24.57a.u for underripe(f0), 19.71 a.ufor ripe 1(f1), 22.91 a.ufor ripe 2(f2), 21.78 a.u.for ripe 3(f3). There are two reasons for higher results obtained user laser, due to their differencesin wavelength, and beam shape.